Knowledge Discovery, Knowledge Engineering and Knowledge Management : 5th International Joint Conference, IC3K 2013, Vilamoura, Portugal, September 19-22, 2013. Revised Selected Papers - Fred, Ana.; Dietz, Jan L.G.; Liu, Kecheng; Filipe, Joaquim; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed proceedings of the 5th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management, IC3K 2013, held in Vilamoura, Portugal, in September 2013. The 27 full papers presented together with two invited papers were carefully reviewed and selected from 239 submissions. The papers are organized in topical sections on knowledge discovery and information retrieval; knowledge engineering and ontology development; knowledge management and information sharing.
Topical sections on knowledge discovery and information retrieval -- Knowledge engineering and ontology development -- Knowledge management and information sharing.
Keywords: Information storage and retrieva; Data mining; Artificial intelligence; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Artificial Intelligence